MELACAK SUMBER LOGAM DI SITUS TAMBLINGAN - I Putu Yuda Haribuana (Balai Arkeologi Bali, 2013)
Archaeological site of Tamblingan had been studied for several steps but still kept a basic thing which has not been revealed, related to the argument that this site was a metal processing site. It was indicated by the existence of metal in this site. In this study, it was traced the existence of metal and natural resources potential in this area. The research was done through some methods namely survey, excavation, photograph and video records and library research. Primary data were analyzed descriptively and qualitatively which reflected lithological condition in that area. From data analysis, it was known that there was metallic mineral element in that area. Besides that, there is also potential of minerals which are still exploited until today.Situs arkeologi Tamblingan telah diteliti selama beberapa tahapan namun masih menyimpan suatu hal yang mendasar yang belum terungkap, terkait dengan pernyataan situs ini merupakan situs olah logam. Hal tersebut adalah keberadaan bahan logam di situs ini. Dalam penelitian ini perlu ditelusuri keberadaan bahan logam dan potensi sumberdaya alam lainnya yang terdapat disini. Penelitian dilakukan dengan metode survei, ekskavasi, perekaman data foto dan video, serta studi kepustakaan. Analisis deskriptif kualitatif dilakukan pada data data primer yang mencerminkan kondisi litologi daerah penelitian. Dari hasil analisis data diketahui bahwa di situs Tamblingan memang terdapat jejak unsur mineral logam, disamping itu terdapat juga potensi bahan galian yang sampai saat ini masih diekploitasi.